2003
DOI: 10.1086/367896
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucosal Recognition ofHelicobacter pyloriIs Independent of Toll‐Like Receptor 4

Abstract: Little is known about the interactions between Helicobacter pylori, which specializes in colonizing the mucin layer that covers the gastric mucosa, and primary gastric epithelial cells. The expression pattern of Toll-like receptors (TLRs) in primary gastric epithelial cells and cell lines was compared. Primary cells did not express TLR4, whereas all cell lines expressed a nonsignaling form of TLR4. Because other cells within the mucosa expressed TLR4, it was next investigated whether H. pylori can be recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 49 publications
6
99
0
4
Order By: Relevance
“…Interestingly, Guillemin et al (34) noted that the genes whose expressions were least effected by the Cag phenotype were those involved in the immune response thus suggesting that Toll-like receptor activation may be directly responsible for the regulation of that subset. Consistent with the studies reported here, a recent report by Bä ckhed et al (15) demonstrated that regulation of gastric mucosal responses to H. pylori is TLR4-independent but cag pathogenicity island-dependent. The role of other TLRs in regulating the response to H. pylori was not addressed in those studies, however.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, Guillemin et al (34) noted that the genes whose expressions were least effected by the Cag phenotype were those involved in the immune response thus suggesting that Toll-like receptor activation may be directly responsible for the regulation of that subset. Consistent with the studies reported here, a recent report by Bä ckhed et al (15) demonstrated that regulation of gastric mucosal responses to H. pylori is TLR4-independent but cag pathogenicity island-dependent. The role of other TLRs in regulating the response to H. pylori was not addressed in those studies, however.…”
Section: Discussionsupporting
confidence: 93%
“…The findings by Schmausser et al (2004) contradict earlier findings by Backhed et al (2003). The latter group examined expression of TLR2, TLR4 and TLR5 in antral biopsies from 20 subjects (six infected with cagA-positive strains, nine with cagA-negative strains and five uninfected).…”
Section: H Pylori-induced Gastric Cancer Modelmentioning
confidence: 63%
“…Several studies have addressed the mRNA levels and protein expression of TLR4 and TLR5 in gastrointestinal cells or in AGS cells [6][7][8][9]13] . In this study, we examined the mRNA levels of TLR4 and TLR5 in gastric epithelial cells (biopsies and AGS cells) in order to determine if significant changes in mRNA levels could be related to the presence of H pylori or differences between the virulence of the strains.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are a family of mammalian homologs of the Drosophila Toll proteins and, in mammalian systems, TLR4 confers responsiveness to Gramnegative lipopolysaccharide (LPS), while TLR5 recognizes flagellin [5] . Previous studies have shown that gastric epithelia express both TLR4 and TLR5 [6][7][8][9] . Here, we studied the mRNA levels of TLR4 and TLR5 in gastric epithelial cells to determine if distinctive changes in the levels of mRNA could be affected by the presence of toxigenic and non-toxigenic (in particular vacA+ strains) H pylori strains.…”
Section: Introductionmentioning
confidence: 99%